Asthma at woman during pregnancy - Kołaczkowska, Małgorzata (Przewodnik Lekarza/Guide for GPs Supplement, 2007)
Asthma bronchial is one the most common conditions complicating pregnancy. Asthma increases the risk of preterm birth, intrauterine growth restriction, low birth weight, congenital malformation and other pregnancy complications. The perinatal prognosis for children born to women with well-controlled asthma is the same as to women without asthma. Generally recommendations for asthma management in pregnant women are the same as the rest of the population (inhaled corticosteroids, β 2 -mimetics, cromones, leukotriene modifiers, rarely theophylline and systemic corticosteroids). However poor asthma control in pregnancy is associated with a higher risk of maternal complications most of the drugs are safety.